A triple star in disarray: multi-epoch observations of T Tauri with VLT-SPHERE and LBT-LUCI - Kasper, Markus; Henning, Thomas; Heidt, Jochen (Astronomy and astrophysics, 2020)
Aims. T Tauri remains an enigmatic triple star for which neither the evolutionary state of the stars themselves, nor the geometry of the complex outflow system is completely understood. Eight-meter class telescopes equipped with state-of-the-art adaptive optics provide the spatial resolution necessary to trace tangential motion of features over a timescale of a few years, and they help to associate them with the different outflows.Methods. We used J-, H-, and K-band high-contrast coronagraphic imaging with VLT-SPHERE recorded between 2016 and 2018 to map reflection nebulosities and obtain high precision near-infrared (NIR) photometry of the triple star. We also present H2 emission maps of the ν = 1-0 S(1) line at 2.122 μm obtained with LBT-LUCI during its commissioning period at the end of 2016.Results. The data reveal a number of new features in the system, some of which are seen in reflected light and some are seen in H2 emission; furthermore, they can all be associated with the main outflows. The tangential motion of the features provides compelling evidence that T Tauri Sb drives the southeast-northwest outflow. T Tauri Sb has recently faded probably because of increased extinction as it passes through the southern circumbinary disk. While Sb is approaching periastron, T Tauri Sa instead has brightened and is detected in all our J-band imagery for the first time.
Gesehen am 21.01.2021